Intestinal microbiota and factors influencing poultry (Research, Society and Development, 2020)
The poultry industry evolved and reached high production performance, with several zootechnical techniques that contributed to the current scenario, including ambience, genetics and diet - all contributing and optimizing the digestive system of the birds. The gastrointestinal tract is a system with several functions and attributions within the organism, among them, digestion of the host, immunity and proper functioning of the system. The gut microbiota has direct effects on metabolic processes and subsequently on the performance of birds. Issues related to microbiota have acquired relevance both for the maintenance and modulation of these microorganisms. One of the maneuvers used to manipulate the intestinal microflora was the use of antibiotics, acting as growth promoters; however, this type of additive, due to sanitary pressure, should be abolished in the coming years, which makes other options appear on the scene, among them, phytogenic additives. Among the latter, essential oils have gained prominence for their beneficial activity in the microbiota as well as their natural composition and non-residual impacts on the process. Based on this, the aim was to review the guidelines that affect the intestinal microbiota in poultry.